Ways of Effective Communication: How to connect efficiently - V. Chinmai Sai, G.; V. Praveen, G. (International Journal of Engineering and Technology, 2018)
Effective Communication is significant for managers in the organizations so as to perform the basic functions of management, i.e., Planning, Organizing, Leading and Controlling. Statistics point to the fact that approximately 85% percent of studentâ€™s success in life is directly attributable to communication skills. That means that no matter how ambitious, how committed, or how highly educated someone is, they still have a low probability of success unless student develop the right communication skills.Communication is a two way process, so improving communication involves both how students send and receive messages.Â Â